"Narrating Palestinian Identity as a ’Writing Back’ Strategy in Novelistic Creativity" - saadi, hanane; souici, nacera (El Omda in Linguistics and Discourse Analysis, 2024)
This study aims at revealing the aspects of narrating the identity in the Palestinian novelistic creative style, as a strategy to respond by writing to what this identity is facing, represented in the attempts to eradicate it and uproot it by the Zionist occupation, which follows systematic policies to obliterate it or even abolish it. For this reason, narrating the identity to mark the existence of the Palestinian resisting identity. Through all this, the Palestinian narrative becomes an awareness-rising text, through which the features of Palestinian identity are determined, and in the light of which its cultural patterns and particularities are represented. This creates counter-narratives that undermine Zionist narratives and dismantle its discourses; therefore, it stands in the way of its hard efforts to eliminate Palestinian identity and Israelize Palestine